Pendidikan Karakter Guru Raudlatul Athfal (RA) Berbasis Kehidupan Lebah - Noor, Fu`ad Arif (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2017)
Picture (citra) of bees is as being polite and full of manners, discipline in carrying out its role, tenacious in producing quality performance, and has a patriotic spirit Bayangkara. Results as inscriptions engraved (atsar) is honey (honey), which is a bee product that has a very high value. Honey is assumed as a result of the totality of the bees performance. If the teacher is able to learn from the bees, the honey is meaningful as follows: First, teachers are able to create high performance through their competence. Second, the teacher strives to remain on the path to the existing rules (On the track) via implanted in his personal commitment. Third, a means that is believed Networking prowess in realizing the vision and mission as well as private institutions. Fourth, the teacher is able to integrate his mind and heart to produce a sense of fun and love on the job (Enjoy at work) which is mandated to him. And fifth, God willing, capable to be an example (You must be a good model) for the working environment especially in Raudlatul Athfal (RA)